A fluorescent probe with an aggregation-enhanced emission feature for real-time monitoring of low carbon dioxide levels1. Issue 29 (7th August 2015) - Wang, Huan; Chen, Didi; Zhang, Yahui; Liu, Pai; Shi, Jianbing; Feng, Xiao; Tong, Bin; Dong, Yuping
<x xml:space="preserve">Abstract</x> The presented method provides a facile and rapid approach to detect low levels of CO2 with high sensitivity, selectivity and reversibility.